Blood lipid concentrations and other cardiovascular risk factors: distribution, prevalence, and detection in Britain. Issue 6638 (18th June 1988) - Mann, J I; Lewis, B; Shepherd, J; Winder, A F; Fenster, S; Rose, L; Morgan, B
Abstract : To establish the distribution of blood lipid concentrations and the prevalences of other risk factors for cardiovascular disease in Britain 12 092 men and women aged 25-59 in Glasgow, Leicester, London, and Oxford were studied. Subjects were selected by opportunistic case finding, in which patients consulting their general practitioner for any reason were offered a health check by appointment, or random selection from age-sex registers, in which an invitation for a health check was posted. The overall rate of response was 73%, being 91-94% by opportunistic case finding and 36-63% by random selection. At the health check subjects answered a brief questionnaire about risk factors for cardiovascular disease, and their height, weight, and blood pressure were recorded; a blood sample was taken for measuring plasma concentrations of cholesterol, triglyceride, high density lipoprotein cholesterol, and glucose. The mean cholesterol concentrations were 5·9 (SD 1·2) and 5·8 (1·2) mmol/l in men and women, respectively. In London the mean value was 5·5 (1·2) mmol/l for both men and women and was significantly lower than mean values in the three other centres, among which there were no significant differences. In men and women aged 25-29 concentrations were similar but they increased in men until the age of 45-49, after which they showed no further increase; in women concentrations did not increase until the age of 40-44 and by the age of 50-59 values were higher than in men. Mean triglyceride concentrations were significantly higher in men than in women (1·8 (1·4) v 1·3 (0·9) mmol/l, respectively), and trends with age were similar to those for cholesterol concentrations, except that at no age were values higher in women than in men. Mean triglyceride values overall were higher in Glasgow and London than in Oxford and Leicester. Body mass index was higher in Glasgow and London than in the other two centres and correlated with systolic and diastolic blood pressures and triglyceride concentration. In addition, subjects in Glasgow smoked significantly more than those in the other centres. These observations could contribute to the higher rate of coronary heart disease in Glasgow. Plasma lipid concentrations and the prevalences of other risk factors for cardiovascular disease were similar in subjects selected by opportunistic case finding and by random selection. In Britain cholesterol values have changed little during the past 12 years despite dietary recommendations and health education. Identifying subjects at particularly high risk of coronary heart disease is required to supplement advice to the general population to reduce the prevalence of this disease. Opportunistic case finding would be an appropriate method of identifying such subjects in general practice, although none of the potential markers for hyperlipidaemia was particularly useful in identifying all subjects at high risk.